Determinants of Employee Job Satisfaction in a Public Organisation in the Province of KwaZulu-Natal - Mbhele, Ncamisile; Matsiliza, Noluthando S. (Journal of Reviews on Global Economics, 2019)
This study assesses factors that determined employee job satisfaction at the South African Social Security Agency (SASSA) in the Pietermaritzburg office of the KwaZulu-Natal Province. The intention of this study is to recommend workable strategies and mechanisms that can be considered by SASSA as they enhance their organisational development and employee standards. The two-factor theory of Herzberg was applied to comprehend the motivating issues that might determine the fulfilment and discontentment of workers at work. The case of SASSA is used to fill a gap in the literature regarding work values and to provide lessons that can be learnt by other organisations that aspire to improve employee job satisfaction. In order to respond to the aim of this study, the data was collected and analysed using a mixed research methodology. A purposive sample was drawn from the employees who had interest and understanding of job satisfaction using mainly interviews and questionnaires. The findings that the political and socio-economic factors have a potential to limit SASSA from offering a suitable and viable healthy working environment, hence job satisfaction might not be realised. Even though it was revealed that some employees were dissatisfied with their working conditions, none of them were planning to leave their jobs. The findings of this study contribute towards the understanding of job satisfaction aspects of human resources management.